Anti-aging material prepared from recycled polypropylene and preparation method of anti-aging material

By melting and blending materials such as recovered polypropylene, modified ethylene-vinyl acetate copolymer and modified talc powder, it forms a cross-linking network, which solves the problem of aging of recovered polypropylene materials and improves its mechanics and aging resistance, extend service life and enhance UV resistance, thermal oxygen resistance and flame retardant properties.

CN119119635AInactive Publication Date: 2024-12-13肇庆市合亚科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411401652.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The recycled polypropylene material ages during use, resulting in a decrease in mechanical properties, making it difficult to put it into use again, and lacks aging resistance.

Method used

The recycled polypropylene, modified ethylene-vinyl acetate copolymer, modified talc powder and end-hydrogen silicone oil are used for melt blending and extrusion, and cross-linking network is formed through aldehyde synthesis, hydroxylation and hydrogen silicone reaction. Reinforce the anti-aging properties of the material.

Benefits of technology

It significantly improves the mechanical properties and aging resistance of recovered polypropylene materials, extends service life, and enhances UV resistance, thermal oxygen resistance and flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075441100000111
    Figure BDA0005075441100000111
Patent Text Reader

Abstract

The invention discloses an anti-aging material prepared from recycled polypropylene and a preparation method of the anti-aging material, and relates to the field of materials. The anti-aging material prepared by the invention is prepared by carrying out melt blending on recycled polypropylene, modified talcum powder, a modified ethylene-vinyl acetate copolymer and chloroplatinic acid and then carrying out extrusion granulation. The modified ethylene-vinyl acetate copolymer is obtained by reacting an aldehyde alcoholysis ethylene-vinyl acetate copolymer with a 4-hydroxy-2, 2, 6, 6-tetramethylpiperidine-1-oxygen free radical and then reacting with maleic anhydride, and the modified ethylene-vinyl acetate copolymer is obtained by reacting an aldehyde alcoholysis ethylene-vinyl acetate copolymer with a 4-hydroxy-2, 2, 6, 6-tetramethylpiperidine-1-oxygen free radical; the modified talcum powder is prepared by grafting allyl phosphamide to talcum powder modified by (3-mercaptopropyl) trimethoxysilane and then reacting with a tertiary amine functional monomer; the tertiary amine functional monomer is prepared by carrying out a reaction on (4-chloro-6-methylpyrimidine-2-yl) phenol and 4-(N, N-dimethyl) aniline magnesium bromide; the aging-resistant material prepared from the recycled polypropylene has good mechanical properties, aging resistance, flame retardance and antibacterial property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to an aging-resistant material prepared by recycling polypropylene and a preparation method thereof. Background Art

[0002] Plastics are widely used due to their many advantages such as low density, light weight, and stable chemical properties. Polypropylene is currently the second most common plastic and the main raw material for plastic products such as plastic buckets, plastic chairs, and plastic lunch boxes. With the development of industries such as construction, daily necessities, and packaging, waste polypropylene has become one of the waste polymer materials with a larger output. At present, the main ways to deal with waste polypropylene are: landfill, incineration for energy, catalytic cracking to prepare fuel, recycling, etc. Considering the technical feasibility, cost, energy consumption, and environmental protection factors in the process of treating waste polypropylene, recycling polypropylene and preparing it into polymer materials again is a very environmentally friendly way to deal with waste plastics.

[0003] Most of the recycled waste polypropylene comes from waste plastics. After use, plastics will inevitably age to a certain extent and their molecular weight will decrease. At the same time, due to the migration of processing aids or additives, the mechanical properties and other properties of waste plastics will decrease. Therefore, it is necessary to improve the mechanical properties of recycled polypropylene so that the recycled polypropylene material can be put back into use. At the same time, it is also necessary to improve the aging resistance of recycled polypropylene to enhance its service life. Summary of the invention

[0004] The purpose of the present invention is to provide an aging-resistant material prepared by recycling polypropylene and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an anti-aging material prepared by recycled polypropylene, comprising the following raw materials in parts by mass: 100 parts of recycled polypropylene, 5-7 parts of modified ethylene-vinyl acetate copolymer, 10-12 parts of modified talcum powder, 5-7 parts of terminal hydrogen silicone oil and 0.2-0.3 parts of chloroplatinic acid. The above raw materials are mixed evenly, melt-blended, extruded and granulated to obtain the anti-aging material prepared by recycled polypropylene.

[0007] Preferably, the modified ethylene-vinyl acetate copolymer is obtained by reacting alcoholysed ethylene-vinyl acetate copolymer with sodium periodate, followed by reaction with 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, and then with maleic anhydride.

[0008] Preferably, the modified talc is prepared by grafting allyl phosphoramide onto talc modified with (3-mercaptopropyl)trimethoxysilane and reacting with a tertiary amine functional monomer; the tertiary amine functional monomer is prepared by reacting (4-chloro-6-methylpyrimidin-2-yl)phenol and 4-(N,N-dimethyl)anilinium magnesium bromide.

[0009] A method for preparing an aging-resistant material by recycling polypropylene, characterized in that it comprises the following preparation steps:

[0010] (1) under nitrogen protection, at 60° C., mixing alcoholyzed ethylene-vinyl acetate copolymer and toluene in a mass ratio of 1:80 for 30-40 minutes, adding sodium periodate in an amount of 0.3-0.5 times the mass of the alcoholyzed ethylene-vinyl acetate copolymer, reacting for 1-2 hours, adding ethylene glycol in an amount of 0.05 times the volume of toluene, and continuing the reaction for 30-40 minutes, adding ethanol in an amount of 3-4 times the volume of toluene for precipitation, filtering, washing with ethanol for 3-4 times, and drying at 30° C. for 6-8 hours to obtain a aldehyded ethylene-vinyl acetate copolymer;

[0011] (2) 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, aldehyde-modified ethylene-vinyl acetate copolymer, cuprous chloride and toluene are mixed in a mass ratio of 1:(2-3):(0.02-0.03):(100-110), and a 30% hydrogen peroxide solution having a mass fraction of 2-2.5 times the mass of the 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical is added dropwise at 10-15° C. at a rate of 0.6 mL / min. After the addition is completed, the temperature is raised to 20-25° C. and the reaction is continued for 10-12 hours. After the reaction is completed, the toluene is removed by distillation under reduced pressure to obtain a pre-modified ethylene-vinyl acetate copolymer;

[0012] (3) mixing the pre-modified ethylene-vinyl acetate copolymer, maleic anhydride, p-toluenesulfonic acid, and N,N-dimethylformamide in a mass ratio of 1:(0.5-0.6):0.01:100, heating to 60-70° C. for reaction for 5-6 hours, adding pure water 3-4 times the mass of N,N-dimethylformamide, filtering and washing with pure water for 3-4 times, and drying at 60° C. for 6-8 hours to obtain a modified ethylene-vinyl acetate copolymer;

[0013] (4) Under nitrogen protection, (4-chloro-6-methylpyrimidin-2-yl)phenol, 4-(N,N-dimethyl)aniline magnesium bromide, and tetrahydrofuran are mixed in a mass ratio of 1:(1.1-1.2):(20-30), stirred for 2-3 hours, and an equal volume of pure water as tetrahydrofuran is added to quench the reaction, extracted with ether, dried over anhydrous sodium sulfate, and finally vacuum evaporated to obtain a tertiary amine functional monomer;

[0014] (5) Pretreated talc, allyl phosphoramide, benzoin dimethyl ether, and N,N-dimethylformamide were mixed in a mass ratio of 1:(2-3):(0.01-0.02):(20-30), reacted under ultraviolet light for 20-30 minutes, the ultraviolet light power was 8 W, and the light source distance was 10 cm, filtered and washed with pure water for 3-4 times, and dried at 60° C. for 6-8 hours to obtain pre-modified talc;

[0015] (6) Pre-modified talc, tertiary amine functional monomer, potassium hydroxide, and N,N-dimethylformamide are mixed in a mass ratio of 1:(2-3):(0.1-0.2):(20-30), reacted at 70-80° C. for 2-3 h, filtered, washed with pure water for 3-4 times, and dried at 60° C. for 6-8 h to obtain modified talc;

[0016] (7) Weigh the following raw materials by mass: 100 parts of recycled polypropylene, 5-7 parts of modified ethylene-vinyl acetate copolymer, 10-12 parts of modified talc, 5-7 parts of end-hydrogen silicone oil, and 0.2-0.3 parts of chloroplatinic acid, mix the raw materials, add them into a twin-screw extruder for blending and extrusion, the melting temperature is 170-190° C., and after extrusion, send them into a pelletizer for granulation to obtain recycled polypropylene for preparing aging-resistant material.

[0017] Preferably, the preparation method of the alcoholyzed ethylene-vinyl acetate copolymer in step (1) is: mixing ethylene-vinyl acetate copolymer and toluene at a mass ratio of 1:16 at 60° C. for 30 minutes, adding a sodium hydroxide solution with a volume of 0.5 times that of toluene and reacting for 2 hours, cooling to room temperature after the reaction is completed, filtering and washing with ethanol for 4 times, and drying at 30° C. for 8 hours to obtain an alcoholyzed ethylene-vinyl acetate copolymer.

[0018] Preferably, the ethylene-vinyl acetate copolymer is EVA resin with a grade of 150; and the sodium hydroxide solution is prepared by mixing sodium hydroxide and toluene in a mass ratio of 1:20.

[0019] Preferably, the preparation method of the pretreated talc powder in step (5) is: (3-mercaptopropyl)trimethoxysilane and talc powder are mixed in a mass ratio of 1:(0.7-0.8) and put into a high-speed mixer, and mixed at a high speed of 100 Hz for 5-10 minutes to obtain the pretreated talc powder.

[0020] Preferably, the preparation method of the allyl phosphoramide in step (5) is: weighing 1-chloro-4-dichlorophosphorylbenzene and allylamine in a molar ratio of 1:(3-3.5); under nitrogen protection, mixing 1-chloro-4-dichlorophosphorylbenzene, acetonitrile and triethylamine in a mass ratio of 1:(10-12):(0.3-0.5), then adding allylamine, reacting at room temperature for 5-6h, and removing acetonitrile by vacuum rotary evaporation to obtain allyl phosphoramide.

[0021] Preferably, the source of the recycled polypropylene in step (7) is crushed polypropylene lunch boxes, polypropylene plastic chairs, and polypropylene plastic barrels; and the hydrogen content of the hydrogen-terminated silicone oil is 0.05%.

[0022] Preferably, the talc powder has a fineness of 1250 mesh.

[0023] The aging-resistant material prepared by the invention is prepared by melt-blending recycled polypropylene, modified talcum powder, modified ethylene-vinyl acetate copolymer and chloroplatinic acid, and then extruding and granulating. The modified ethylene-vinyl acetate copolymer is obtained by reacting an aldehyde-modified alcoholysed ethylene-vinyl acetate copolymer with 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, and then reacting with maleic anhydride. The modified talcum powder is obtained by grafting allyl phosphoramide with talcum powder modified with (3-mercaptopropyl)trimethoxysilane, and then reacting with a tertiary amine functional monomer. The tertiary amine functional monomer is obtained by reacting (4-chloro-6-methylpyrimidin-2-yl)phenol with 4-(N,N-dimethyl)anilinium magnesium bromide.

[0024] Firstly, the mechanical properties and processing properties of recycled polypropylene can be improved by compounding ethylene-ethyl acetate copolymer with recycled polypropylene. The ethylene-ethyl acetate copolymer is subjected to alcoholysis and then oxidized with an oxidant, sodium periodate, to obtain an aldehyde group. The aldehyde group reacts with a 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical to graft a hindered amine structure on the ethylene-vinyl acetate side chain. The hindered amine structure can endow the material with the ability to resist thermal oxidative aging by capturing free radicals. The hydroxyl group on the 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical reacts with maleic anhydride to open the maleic anhydride ring so that the side chain of the ethylene-vinyl acetate copolymer carries both a double bond and a carboxylic acid group.

[0025] Secondly, 2-(4-chloro-6-methylpyrimidin-2-yl)phenol and Grignard reagent 4-(N,N-dimethyl)anilinium magnesium bromide react to generate a tertiary amine monomer. The nitrogen element on the pyrimidine on the tertiary amine monomer and the ortho-phenolic hydroxyl structure form an intramolecular chelate ring that can effectively absorb ultraviolet rays, convert light energy into heat energy, and give the material good resistance to ultraviolet aging. Talc, as an inorganic filler, can significantly enhance the strength and hardness of the material. Talc is modified with a silane coupling agent (3-mercaptopropyl) trimethoxysilane so that the surface of talc has a thiol group. The thiol group and allyl amide undergo a thiol-alkenyl click reaction so that the surface of talc is grafted with a phosphorus element with a flame retardant function. The chlorine on the allyl amide undergoes a quaternization reaction with the tertiary amine monomer to generate a quaternary ammonium salt structure. The quaternary ammonium salt structure can give the material certain antibacterial properties.

[0026] Finally, recycled polypropylene, modified ethylene-vinyl acetate copolymer, modified talcum powder, terminal hydrogen silicone oil, and chloroplatinic acid are melt-blended and extruded and granulated to obtain recycled polypropylene for the preparation of aging-resistant material; the positive charge of quaternary ammonium salt on the modified talcum powder and the carboxyl group of the side chain of the modified ethylene-vinyl acetate copolymer can improve the dispersibility of the modified talcum powder in the material through the interaction between positive and negative charges; the silicon-oxygen bond in the terminal hydrogen silicone oil can improve the thermal stability of the material, and the terminal hydrogen silicone oil undergoes a silylation reaction with the modified talcum powder and the modified ethylene-vinyl acetate copolymer containing carbon-carbon double bonds on the surface in the presence of chloroplatinic acid to form a cross-linked network, which can improve the mechanical properties of the material. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The ethylene-vinyl acetate copolymer used in the following embodiments and comparative examples is EVA resin with a grade of 150; the recycled polypropylene source is polypropylene lunch boxes, polypropylene plastic chairs, and polypropylene plastic barrel crushed materials; the hydrogen content of the hydrogen-terminated silicone oil is 0.05%; the fineness of talcum powder is 1250 mesh; and the sodium hydroxide solution is prepared by mixing sodium hydroxide and toluene in a mass ratio of 1:20.

[0029] Embodiment 1:

[0030] A method for preparing an aging-resistant material by recycling polypropylene comprises the following preparation steps:

[0031] (1) Mixing ethylene-vinyl acetate copolymer and toluene at a mass ratio of 1:16 at 60° C. for 30 minutes, adding a sodium hydroxide solution with a volume of 0.5 times the volume of toluene to react for 2 hours, cooling to room temperature after the reaction, filtering with suction and washing with ethanol 4 times, and drying at 30° C. for 8 hours to obtain alcoholyzed ethylene-vinyl acetate copolymer; mixing alcoholyzed ethylene-vinyl acetate copolymer and toluene at a mass ratio of 1:80 at 60° C. for 40 minutes under nitrogen protection, adding sodium periodate with a mass of 0.3 times the mass of the alcoholyzed ethylene-vinyl acetate copolymer, reacting for 2 hours, adding ethylene glycol with a volume of 0.05 times the volume of toluene to continue the reaction for 40 minutes, adding ethanol with a volume of 4 times the volume of toluene to precipitate, filtering with suction and washing with ethanol 4 times, and drying at 30° C. for 8 hours to obtain aldehyded ethylene-vinyl acetate copolymer;

[0032] (2) 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, formaldehyde-modified ethylene-vinyl acetate copolymer, cuprous chloride and toluene are mixed in a mass ratio of 1:2:0.02:10, and a 30% hydrogen peroxide solution having a mass fraction of twice that of the 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical is added dropwise at 15° C. at a rate of 0.6 mL / min. After the addition is completed, the temperature is raised to 25° C. and the reaction is continued for 12 h. After the reaction is completed, toluene is removed by distillation under reduced pressure to obtain a pre-modified ethylene-vinyl acetate copolymer;

[0033] (3) mixing the pre-modified ethylene-vinyl acetate copolymer, maleic anhydride, p-toluenesulfonic acid, and N,N-dimethylformamide in a mass ratio of 1:0.5:0.01:100, heating to 70°C for reaction for 6 hours, adding pure water 3 times the mass of N,N-dimethylformamide, filtering and washing with pure water 4 times, and drying at 60°C for 8 hours to obtain a modified ethylene-vinyl acetate copolymer;

[0034] (4) Under nitrogen protection, (4-chloro-6-methylpyrimidin-2-yl)phenol, 4-(N,N-dimethyl)aniline magnesium bromide, and tetrahydrofuran were mixed in a mass ratio of 1:1.1:20, stirred for 3 hours, and pure water in an equal volume to tetrahydrofuran was added to quench the reaction, extracted with ether, dried over anhydrous sodium sulfate, and finally vacuum evaporated to obtain a tertiary amine functional monomer;

[0035] (5) (3-mercaptopropyl) trimethoxysilane and talc are mixed in a mass ratio of 1:0.7 and put into a high-speed mixer, and mixed at a high speed of 100 Hz for 10 minutes to obtain pretreated talc; 1-chloro-4-dichlorophosphorylbenzene and allylamine are weighed in a molar ratio of 1:3; under nitrogen protection, 1-chloro-4-dichlorophosphorylbenzene, acetonitrile and triethylamine are mixed in a mass ratio of 1:10:0.3, and allylamine is added, and the mixture is reacted at room temperature for 6 hours, and the acetonitrile is removed by vacuum rotary evaporation to obtain allyl phosphoramide; pretreated talc, allyl phosphoramide, benzoin dimethyl ether, and N,N-dimethylformamide are mixed in a mass ratio of 1:2:0.01:20, and the mixture is reacted under ultraviolet light for 30 minutes, the ultraviolet light power is 8W, and the light source distance is 10 cm, and the mixture is filtered and washed with pure water 4 times, and dried at 60°C for 8 hours to obtain pre-modified talc;

[0036] (6) Pre-modified talc, tertiary amine functional monomer, potassium hydroxide, and N,N-dimethylformamide were mixed in a mass ratio of 1:2:0.1:20, reacted at 80° C. for 3 h, filtered, washed with pure water for 4 times, and dried at 60° C. for 8 h to obtain modified talc;

[0037] (7) Weigh the following raw materials by mass: 100 parts of recycled polypropylene, 5 parts of modified ethylene-vinyl acetate copolymer, 10 parts of modified talcum powder, 5 parts of end-hydrogen silicone oil, and 0.2 parts of chloroplatinic acid. Mix the raw materials and add them into a twin-screw extruder for blending and extrusion. The melting temperature is 190° C. After extrusion, the mixture is sent to a pelletizer for pelletization to obtain recycled polypropylene for preparing an aging-resistant material.

[0038] Embodiment 2:

[0039] A method for preparing an aging-resistant material by recycling polypropylene comprises the following preparation steps:

[0040] (1) Mixing ethylene-vinyl acetate copolymer and toluene at a mass ratio of 1:16 at 60° C. for 30 minutes, adding a sodium hydroxide solution with a volume of 0.5 times the volume of toluene to react for 2 hours, cooling to room temperature after the reaction, filtering with suction and washing with ethanol 4 times, and drying at 30° C. for 8 hours to obtain alcoholyzed ethylene-vinyl acetate copolymer; mixing alcoholyzed ethylene-vinyl acetate copolymer and toluene at a mass ratio of 1:80 at 60° C. for 35 minutes under nitrogen protection, adding sodium periodate with a volume of 0.4 times the mass of the alcoholyzed ethylene-vinyl acetate copolymer, reacting for 1.5 hours, adding ethylene glycol with a volume of 0.05 times the volume of toluene to continue the reaction for 35 minutes, adding ethanol with a volume of 3.5 times the volume of toluene to precipitate, filtering with suction and washing with ethanol 3 times, and drying at 30° C. for 7 hours to obtain aldehyded ethylene-vinyl acetate copolymer;

[0041] (2) 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, formaldehyde-modified ethylene-vinyl acetate copolymer, cuprous chloride and toluene are mixed in a mass ratio of 1:2.5:0.025:105, and a 30% hydrogen peroxide solution having a mass fraction of 2.3 times the mass of 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical is added dropwise at 13° C. at a rate of 0.6 mL / min. After the addition is completed, the temperature is raised to 23° C. and the reaction is continued for 11 hours. After the reaction is completed, toluene is removed by distillation under reduced pressure to obtain a pre-modified ethylene-vinyl acetate copolymer;

[0042] (3) mixing the pre-modified ethylene-vinyl acetate copolymer, maleic anhydride, p-toluenesulfonic acid, and N,N-dimethylformamide in a mass ratio of 1:0.55:0.01:100, heating to 65°C for reaction for 5.5 hours, adding pure water 3.5 times the mass of N,N-dimethylformamide, filtering and washing with pure water for 3 times, and drying at 60°C for 7 hours to obtain a modified ethylene-vinyl acetate copolymer;

[0043] (4) Under nitrogen protection, (4-chloro-6-methylpyrimidin-2-yl)phenol, 4-(N,N-dimethyl)aniline magnesium bromide, and tetrahydrofuran were mixed in a mass ratio of 1:1.15:25, stirred for 2.5 hours, and pure water in an amount equal to that of tetrahydrofuran was added to quench the reaction, extracted with ether, dried over anhydrous sodium sulfate, and finally vacuum evaporated to obtain a tertiary amine functional monomer;

[0044] (5) (3-mercaptopropyl)trimethoxysilane and talc were mixed in a mass ratio of 1:0.75 and added into a high-speed mixer, and mixed at a high speed of 100 Hz for 7 minutes to obtain pretreated talc; 1-chloro-4-dichlorophosphorylbenzene and allylamine were weighed in a molar ratio of 1:3.2; 1-chloro-4-dichlorophosphorylbenzene, acetonitrile and triethylamine were mixed in a mass ratio of 1:11:0.4 under nitrogen protection, and olefin was added. Propylamine, react at room temperature for 5.5 hours, and remove acetonitrile by vacuum rotary evaporation to obtain allyl phosphoramide; pretreated talc, allyl phosphoramide, benzoin dimethyl ether, and N,N-dimethylformamide are mixed at a mass ratio of 1:2.5:0.015:25, and react under ultraviolet light for 25 minutes, the ultraviolet light power is 8W, and the light source distance is 10 cm, filtered and washed with pure water for 3 times, and dried at 60°C for 7 hours to obtain pre-modified talc;

[0045] (6) pre-modified talc, tertiary amine functional monomer, potassium hydroxide, and N,N-dimethylformamide were mixed in a mass ratio of 1:2.5:0.015:25, reacted at 75° C. for 2.5 h, filtered, washed with pure water for 3 times, and dried at 60° C. for 7 h to obtain modified talc;

[0046] (7) Weigh the following raw materials by mass: 100 parts of recycled polypropylene, 6 parts of modified ethylene-vinyl acetate copolymer, 11 parts of modified talcum powder, 6 parts of end-hydrogen silicone oil, and 0.25 parts of chloroplatinic acid, mix the raw materials and add them into a twin-screw extruder for blending and extrusion at a melting temperature of 170-190° C. After extrusion, send them into a pelletizer for granulation to obtain recycled polypropylene for preparing an aging-resistant material.

[0047] Embodiment 3:

[0048] A method for preparing an aging-resistant material by recycling polypropylene comprises the following preparation steps:

[0049] (1) Mixing ethylene-vinyl acetate copolymer and toluene at a mass ratio of 1:16 at 60° C. for 30 minutes, adding a sodium hydroxide solution with a volume of 0.5 times the volume of toluene to react for 2 hours, cooling to room temperature after the reaction, filtering with suction and washing with ethanol 4 times, and drying at 30° C. for 8 hours to obtain alcoholyzed ethylene-vinyl acetate copolymer; mixing alcoholyzed ethylene-vinyl acetate copolymer and toluene at a mass ratio of 1:80 at 60° C. for 30 minutes under nitrogen protection, adding sodium periodate with a volume of 0.5 times the mass of the alcoholyzed ethylene-vinyl acetate copolymer, reacting for 1 hour, adding ethylene glycol with a volume of 0.05 times the volume of toluene to continue the reaction for 30 minutes, adding ethanol with a volume of 4 times the volume of toluene to precipitate, filtering with suction and washing with ethanol 3 times, and drying at 30° C. for 6 hours to obtain aldehyded ethylene-vinyl acetate copolymer;

[0050] (2) 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, aldehyde-modified ethylene-vinyl acetate copolymer, cuprous chloride and toluene are mixed in a mass ratio of 1:3:0.03:110, and a 30% hydrogen peroxide solution having a mass fraction of 2-2.5 times the mass of 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical is added dropwise at 10° C., and the addition speed is 0.6 mL / min. After the addition is completed, the temperature is raised to 20° C., and the reaction is continued for 10 hours. After the reaction is completed, the toluene is removed by distillation under reduced pressure to obtain a pre-modified ethylene-vinyl acetate copolymer;

[0051] (3) mixing the pre-modified ethylene-vinyl acetate copolymer, maleic anhydride, p-toluenesulfonic acid, and N,N-dimethylformamide in a mass ratio of 1:0.6:0.01:100, heating to 60°C for reaction for 5 hours, adding pure water 4 times the mass of N,N-dimethylformamide, filtering and washing with pure water 3 times, and drying at 60°C for 6 hours to obtain a modified ethylene-vinyl acetate copolymer;

[0052] (4) Under nitrogen protection, (4-chloro-6-methylpyrimidin-2-yl)phenol, 4-(N,N-dimethyl)aniline magnesium bromide, and tetrahydrofuran were mixed in a mass ratio of 1:1.2:30, stirred for 2 h, and pure water in an equal volume to tetrahydrofuran was added to quench the reaction, extracted with ether, dried over anhydrous sodium sulfate, and finally vacuum evaporated to obtain a tertiary amine functional monomer;

[0053] (5) (3-mercaptopropyl) trimethoxysilane and talc are mixed in a mass ratio of 1:0.8 and put into a high-speed mixer, and mixed at a high speed of 100 Hz for 5 minutes to obtain pretreated talc; 1-chloro-4-dichlorophosphorylbenzene and allylamine are weighed in a molar ratio of 1:3.5; under nitrogen protection, 1-chloro-4-dichlorophosphorylbenzene, acetonitrile and triethylamine are mixed in a mass ratio of 1:12:0.5, and allylamine is added, and the mixture is reacted at room temperature for 5 hours, and the acetonitrile is removed by vacuum rotary evaporation to obtain allyl phosphoramide; pretreated talc, allyl phosphoramide, benzoin dimethyl ether, and N,N-dimethylformamide are mixed in a mass ratio of 1:3:0.02:30, and the mixture is reacted under ultraviolet light for 20 minutes, the ultraviolet light power is 8W, and the light source distance is 10 cm, and the mixture is filtered and washed with pure water 3 times, and dried at 60°C for 6 hours to obtain pre-modified talc;

[0054] (6) Pre-modified talc, tertiary amine functional monomer, potassium hydroxide, and N,N-dimethylformamide were mixed in a mass ratio of 1:3:0.2:30, reacted at 70° C. for 2 h, filtered, washed with pure water for 3 times, and dried at 60° C. for 6 h to obtain modified talc;

[0055] (7) Weigh the following raw materials by mass: 100 parts of recycled polypropylene, 7 parts of modified ethylene-vinyl acetate copolymer, 12 parts of modified talcum powder, 7 parts of end-hydrogen silicone oil, and 0.3 parts of chloroplatinic acid, mix the raw materials and add them into a twin-screw extruder for blending and extrusion at a melting temperature of 170°C. After extrusion, send them into a pelletizer for granulation to obtain recycled polypropylene for preparing an aging-resistant material.

[0056] Comparative Example 1:

[0057] The difference between the preparation method of the aging-resistant material prepared by recycling polypropylene in Comparative Example 1 and Example 2 is that it does not contain steps (2) and (3), and step (1) is modified as follows: ethylene-vinyl acetate copolymer and toluene are mixed at a mass ratio of 1:16 at 60° C. for 30 minutes, a sodium hydroxide solution with a volume of 0.5 times that of toluene is added to react for 2 hours, and after the reaction is completed, the mixture is cooled to room temperature, filtered with suction, washed with ethanol 4 times, and dried at 30° C. for 8 hours to obtain alcoholyzed ethylene-vinyl acetate copolymer; under nitrogen protection, the alcoholyzed ethylene-vinyl acetate copolymer and toluene are mixed at a mass ratio of 1:80 at 60° C. for 35 minutes, sodium periodate with a mass of 0.4 times that of the alcoholyzed ethylene-vinyl acetate copolymer is added, and after reacting for 1.5 hours, ethylene glycol with a volume of 0.05 times that of toluene is added to continue reacting for 35 minutes, ethanol with a volume of 3.5 times that of toluene is added for precipitation, filtered with suction, washed with ethanol 3 times, and dried at 30° C. for 7 hours to obtain a modified ethylene-vinyl acetate copolymer;

[0058] Comparative Example 2:

[0059] The preparation method of the recycled polypropylene for preparing the aging-resistant material in Comparative Example 2 differs from that in Example 2 in that it does not contain steps (4), (5) and (6), and step (7) is modified as follows: weigh the following raw materials in parts by mass: 100 parts of recycled polypropylene, 6 parts of modified ethylene-vinyl acetate copolymer, 11 parts of talcum powder, 6 parts of terminal hydrogen silicone oil, and 0.25 parts of chloroplatinic acid; mix the raw materials and add them into a twin-screw extruder for blending and extrusion; the melting temperature is 170-190°C; after extrusion, send them into a pelletizer for granulation to obtain the recycled polypropylene for preparing the aging-resistant material.

[0060] Comparative Example 3:

[0061] The preparation method of the aging-resistant material prepared by recycling polypropylene in Comparative Example 3 is different from that in Example 2 in that it does not contain steps (4) and (6), and step (5) is modified as follows: (3-mercaptopropyl)trimethoxysilane and talc are mixed in a mass ratio of 1:0.75 and put into a high-speed mixer, and mixed at a high speed of 100 Hz for 7 minutes to obtain pretreated talc; 1-chloro-4-dichlorophosphorylbenzene and allylamine are weighed in a molar ratio of 1:3.2; 1-chloro-4-dichlorophosphorylbenzene is added under nitrogen protection. , acetonitrile, and triethylamine are mixed in a mass ratio of 1:11:0.4, and then allylamine is added, and the mixture is reacted at room temperature for 5.5 hours, and the acetonitrile is removed by vacuum rotary evaporation to obtain allyl phosphoramide; the pretreated talc, allyl phosphoramide, benzoin dimethyl ether, and N,N-dimethylformamide are mixed in a mass ratio of 1:2.5:0.015:25, and the mixture is reacted for 25 minutes under ultraviolet light, the ultraviolet light power is 8W, and the light source distance is 10 cm. The mixture is filtered and washed with pure water for 3 times, and dried at 60°C for 7 hours to obtain modified talc;

[0062] Test Example 1:

[0063] Mechanical properties test:

[0064] According to the standard GB / T 1040-2006, the recycled polypropylene obtained in the embodiment and the comparative example was used to prepare the anti-aging material to prepare the sample, and the tensile strength of the sample was tested at a test speed of 50 mm / min and the environment was room temperature. The results are shown in Table 1.

[0065] UV aging resistance test:

[0066] Test method: According to the standard GB / T 1040-2006, the recycled polypropylene prepared in the embodiment and the comparative example is used to prepare the aging-resistant material to make a sample, the sample is laid flat on the sample rack, and the sample rack is placed in the ultraviolet light box parallel to the ultraviolet lamp, and the radiation intensity is 1100W / m 2 The temperature in the box is 60℃, the humidity is 60%, the fabric is 10cm away from the lamp, and the irradiation time is 60h. After the irradiation, the tensile strength retention rate is tested and calculated according to the mechanical properties test method. The results are shown in Table 1.

[0067] Thermal oxygen aging resistance test:

[0068] Test method: According to the standard GB / T 1040-2006, the recycled polypropylene prepared in the embodiment and the comparative example is used to prepare the aging-resistant material to make a sample, the sample is laid flat on the sample rack, and then put into the aging box, the aging temperature is 50°C, the relative humidity is 55%, the ozone concentration is 450pphm, the aging time is 60h, and after the aging is completed, the tensile strength retention rate is tested and calculated according to the mechanical property test method. The results are shown in Table 1.

[0069] Table 1. Test results of mechanical properties

[0070]

[0071] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the aging-resistant material prepared from the recycled polypropylene prepared in the present invention has good mechanical properties and anti-aging properties.

[0072] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Examples 2 and 3, the tensile strength retention rate of Examples 1 to 3 after ultraviolet irradiation is greater than that of Comparative Examples 2 and 3, and the tensile strength retention rate of Examples 1 to 3 after thermal oxidative aging is greater than that of Comparative Example 1 after thermal oxidative aging; it is shown that firstly, the mechanical properties and processing properties of the recycled polypropylene can be improved by compounding ethylene-ethyl acetate copolymer with recycled polypropylene, the ethylene-ethyl acetate copolymer is alcoholyzed, and then oxidized with an oxidant, sodium periodate, to obtain an aldehyde group, the aldehyde group reacts with 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical, and a hindered amine structure is grafted on the ethylene-vinyl acetate side chain, the hindered amine structure can give the material the ability to resist thermal oxidative aging by capturing free radicals, the hydroxyl group on the 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical reacts with maleic anhydride, the maleic anhydride is ring-opened so that the ethylene-vinyl acetate copolymer The side chain carries both a double bond and a carboxylic acid group; secondly, 2-(4-chloro-6-methylpyrimidin-2-yl)phenol and the Grignard reagent 4-(N,N-dimethyl)aniline magnesium bromide react to generate a tertiary amine monomer, and the nitrogen element on the pyrimidine on the tertiary amine monomer and the ortho-phenolic hydroxyl structure form an intramolecular chelate ring that can effectively absorb ultraviolet rays, convert light energy into heat energy, and give the material good resistance to ultraviolet aging; finally, recycled polypropylene, modified ethylene-vinyl acetate copolymer, modified talc, terminal hydrogen silicone oil, and chloroplatinic acid are melt-blended and extruded to granulate to prepare recycled polypropylene for aging-resistant materials; the positive charge of the quaternary ammonium salt on the modified talc and the carboxyl group of the side chain of the modified ethylene-vinyl acetate copolymer can improve the dispersibility of the modified talc in the material through the interaction between positive and negative charges; the terminal hydrogen silicone oil undergoes a hydrosilylation reaction with the modified talc and the modified ethylene-vinyl acetate copolymer containing carbon-carbon double bonds on the surface in the presence of chloroplatinic acid to form a cross-linked network, which can improve the mechanical properties of the material.

[0073] Test Example 2:

[0074] Flame retardant performance test:

[0075] Test method: The examples and comparative examples were prepared into standard samples according to GB / T 2048, and the limiting oxygen index of the samples was tested. The results are shown in Table 2.

[0076] Table 2. Test results of flame retardant properties

[0077] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 31.66 Comparative Example 1 31.25 Example 2 32.14 Comparative Example 2 25.32 Example 3 31.74 Comparative Example 3 31.33

[0078] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the aging-resistant material prepared from the recycled polypropylene prepared in the present invention has good flame retardant properties.

[0079] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the talc is modified with a silane coupling agent (3-mercaptopropyl) trimethoxysilane so that the surface of the talc has a thiol group, and the thiol group and allyl amide undergo a thiol-alkenyl click reaction so that the surface of the talc is grafted with phosphorus elements having a flame retardant function, which can give the material good combustion-supporting properties.

[0080] Test Example 3:

[0081] Antibacterial performance test:

[0082] Test method: The aging-resistant material prepared from the recycled polypropylene obtained in the embodiment and the comparative example was prepared into a 6 mm circular slice; the circular slice was placed on an agar medium coated with bacterial solution, inverted in a constant temperature incubator at 37°C for culture, taken out after 24 hours, and the diameter of the inhibition zone was measured and recorded. Staphylococcus aureus was selected for the bacterial solution, and the larger the diameter, the better the antibacterial performance. The results are shown in Table 3.

[0083] Table 3. Test results of antibacterial properties

[0084] Diameter of inhibition zone / mm Diameter of inhibition zone / mm Example 1 10.3 Comparative Example 1 10.1 Example 2 10.2 Comparative Example 2 3.1 Example 3 10.3 Comparative Example 3 3.4

[0085] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the aging-resistant material prepared from the recycled polypropylene prepared in the present invention has good antibacterial properties.

[0086] By comparison, the antibacterial properties of Examples 1 to 3 are greater than those of Comparative Examples 2 and 3, indicating that 2-(4-chloro-6-methylpyrimidin-2-yl)phenol and Grignard reagent 4-(N,N-dimethyl)aniline magnesium bromide react to generate a tertiary amine monomer, talc is modified with a silane coupling agent (3-mercaptopropyl)trimethoxysilane so that the surface of the talc has a thiol group, the thiol group and allylamide undergo a thiol-alkenyl click reaction so that the surface of the talc is grafted with a phosphorus element having a flame retardant function, and the chlorine on the allylamide undergoes a quaternization reaction with the tertiary amine monomer to generate a quaternary ammonium salt structure, and the quaternary ammonium salt structure can give the material certain antibacterial properties.

[0087] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an aging-resistant material by recycling polypropylene, characterized in that: The material comprises the following raw materials by weight: 100 parts of recycled polypropylene, 5-7 parts of modified ethylene-vinyl acetate copolymer, 10-12 parts of modified talc, 5-7 parts of terminal hydrogen silicone oil, and 0.2-0.3 parts of chloroplatinic acid. The above raw materials are mixed, melt-blended, extruded and granulated to obtain recycled polypropylene for preparing aging-resistant material; The modified ethylene-vinyl acetate copolymer is obtained by alcoholysing ethylene-vinyl acetate copolymer, oxidizing it with sodium periodate, reacting it with 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, and then reacting it with maleic anhydride; The modified talc is prepared by grafting allyl phosphoramide onto talc modified with (3-mercaptopropyl)trimethoxysilane and reacting with a tertiary amine functional monomer; the tertiary amine functional monomer is prepared by reacting (4-chloro-6-methylpyrimidin-2-yl)phenol and 4-(N,N-dimethyl)aniline magnesium bromide.

2. A method for preparing an aging-resistant material by recycling polypropylene, characterized in that: The method comprises the following preparation steps: (1) under nitrogen protection, at 60° C., mixing alcoholyzed ethylene-vinyl acetate copolymer and toluene in a mass ratio of 1:80 for 30-40 minutes, adding sodium periodate in an amount of 0.3-0.5 times the mass of the alcoholyzed ethylene-vinyl acetate copolymer, reacting for 1-2 hours, adding ethylene glycol in an amount of 0.05 times the volume of toluene, and continuing the reaction for 30-40 minutes, adding ethanol in an amount of 3-4 times the volume of toluene for precipitation, filtering, washing with ethanol for 3-4 times, and drying at 30° C. for 6-8 hours to obtain a aldehyded ethylene-vinyl acetate copolymer; (2) 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical, aldehyde-modified ethylene-vinyl acetate copolymer, cuprous chloride and toluene are mixed in a mass ratio of 1:(2-3):(0.02-0.03):(100-110), and a 30% hydrogen peroxide solution having a mass fraction of 2-2.5 times the mass of the 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl free radical is added dropwise at 10-15° C. at a rate of 0.6 mL / min. After the addition is completed, the temperature is raised to 20-25° C. and the reaction is continued for 10-12 hours. After the reaction is completed, the toluene is removed by distillation under reduced pressure to obtain a pre-modified ethylene-vinyl acetate copolymer; (3) mixing the pre-modified ethylene-vinyl acetate copolymer, maleic anhydride, p-toluenesulfonic acid, and N,N-dimethylformamide in a mass ratio of 1:(0.5-0.6):0.01:100, heating to 60-70° C. for reaction for 5-6 hours, adding pure water 3-4 times the mass of N,N-dimethylformamide, filtering and washing with pure water for 3-4 times, and drying at 60° C. for 6-8 hours to obtain a modified ethylene-vinyl acetate copolymer; (4) Under nitrogen protection, (4-chloro-6-methylpyrimidin-2-yl)phenol, 4-(N,N-dimethyl)aniline magnesium bromide, and tetrahydrofuran are mixed in a mass ratio of 1:(1.1-1.2):(20-30), stirred for 2-3 hours, and an equal volume of pure water as tetrahydrofuran is added to quench the reaction, extracted with ether, dried over anhydrous sodium sulfate, and finally vacuum evaporated to obtain a tertiary amine functional monomer; (5) Pretreated talc, allyl phosphoramide, benzoin dimethyl ether, and N,N-dimethylformamide were mixed in a mass ratio of 1:(2-3):(0.01-0.02):(20-30), reacted under ultraviolet light for 20-30 minutes, the ultraviolet light power was 8 W, and the light source distance was 10 cm, filtered and washed with pure water for 3-4 times, and dried at 60° C. for 6-8 hours to obtain pre-modified talc; (6) Pre-modified talc, tertiary amine functional monomer, potassium hydroxide, and N,N-dimethylformamide are mixed in a mass ratio of 1:(2-3):(0.1-0.2):(20-30), reacted at 70-80° C. for 2-3 h, filtered, washed with pure water for 3-4 times, and dried at 60° C. for 6-8 h to obtain modified talc; (7) Weigh the following raw materials by mass: 100 parts of recycled polypropylene, 5-7 parts of modified ethylene-vinyl acetate copolymer, 10-12 parts of modified talc, 5-7 parts of end-hydrogen silicone oil, and 0.2-0.3 parts of chloroplatinic acid, mix the raw materials, add them into a twin-screw extruder for blending and extrusion, the melting temperature is 170-190° C., and after extrusion, send them into a pelletizer for granulation to obtain recycled polypropylene for preparing aging-resistant material.

3. The method for preparing an aging-resistant material by recycling polypropylene according to claim 2, characterized in that: The preparation method of the alcoholyzed ethylene-vinyl acetate copolymer in step (1) is as follows: ethylene-vinyl acetate copolymer and toluene are mixed at a mass ratio of 1:16 at 60° C. for 30 minutes, a sodium hydroxide solution with a volume of 0.5 times that of toluene is added and reacted for 2 hours, and after the reaction is completed, the mixture is cooled to room temperature, filtered and washed with ethanol for 4 times, and dried at 30° C. for 8 hours to obtain an alcoholyzed ethylene-vinyl acetate copolymer.

4. The method for preparing an aging-resistant material by recycling polypropylene according to claim 3, characterized in that: The ethylene-vinyl acetate copolymer is EVA resin with a brand number of 150; the sodium hydroxide solution is prepared by mixing sodium hydroxide and toluene in a mass ratio of 1:

20.

5. The method for preparing an aging-resistant material by recycling polypropylene according to claim 2, characterized in that: The preparation method of the pretreated talc powder in step (5) is as follows: (3-mercaptopropyl)trimethoxysilane and talc powder are mixed in a mass ratio of 1:(0.7-0.8) and put into a high-speed mixer, and mixed at a high speed of 100 Hz for 5-10 minutes to obtain the pretreated talc powder.

6. The method for preparing an aging-resistant material by recycling polypropylene according to claim 2, characterized in that: The preparation method of the allyl phosphoramide in step (5) is as follows: 1-chloro-4-dichlorophosphorylbenzene and allylamine are weighed in a molar ratio of 1:(3-3.5); under nitrogen protection, 1-chloro-4-dichlorophosphorylbenzene, acetonitrile and triethylamine are mixed in a mass ratio of 1:(10-12):(0.3-0.5), allylamine is added, the mixture is reacted at room temperature for 5-6 hours, and acetonitrile is removed by vacuum rotary evaporation to obtain allyl phosphoramide.

7. The method for preparing an aging-resistant material by recycling polypropylene according to claim 2, characterized in that: The source of the recycled polypropylene in step (7) is crushed polypropylene lunch boxes, polypropylene plastic chairs, and polypropylene plastic barrels; the hydrogen content of the hydrogen-terminated silicone oil is 0.05%.

8. The method for preparing an aging-resistant material by recycling polypropylene according to claim 5, characterized in that The fineness of the talcum powder is 1250 mesh.